2015
DOI: 10.1249/mss.0000000000000524
|View full text |Cite
|
Sign up to set email alerts
|

Immersion Pulmonary Edema and Comorbidities

Abstract: Cardiopulmonary disease may be a common predisposing factor in IPE in the recreational swimming/diving population, whereas pulmonary hypertension due to extreme exertion may be more important in military cases. Individuals with past history of IPE in our case series had a greater proportion of comorbidities compared to published cases. The role of underlying cardiopulmonary dysfunction may be underestimated, especially in older swimmers and divers. We conclude that an episode of IPE should prompt the evaluatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
79
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(79 citation statements)
references
References 49 publications
0
79
0
Order By: Relevance
“…Peacher et al 17 retrospectively studied 36 participants who experienced swimming-related pulmonary edema, and determined that 72.2% of those who sustained an immersion pulmonary edema event had one or more significant medical conditions (risk factors) at the time of the event compared with only 44.9% in historical controls (p<0.001). The participants for this study were initially recruited for another purpose, and the cases compared using historical controls.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Peacher et al 17 retrospectively studied 36 participants who experienced swimming-related pulmonary edema, and determined that 72.2% of those who sustained an immersion pulmonary edema event had one or more significant medical conditions (risk factors) at the time of the event compared with only 44.9% in historical controls (p<0.001). The participants for this study were initially recruited for another purpose, and the cases compared using historical controls.…”
Section: Resultsmentioning
confidence: 99%
“…Although there are only a small number of lower quality studies, there does appear to be some support that symptoms of SIPE do occur during triathlon or open-water swimming, however, none of these studies has specifically identified SIPE as a cause of swimming-related death. People more likely to have symptoms of SIPE had more than one significant medical condition, such as hypertension 17 20. These symptoms were more likely to occur in longer events and to females 20.…”
Section: Discussionmentioning
confidence: 99%
“…Auscultation reveals bibasilar rales, with a pulmonary oedema pattern seen on the chest radiograph. The disorder is transient and clears on chest radiography in 7 days [45]. It is common to find decreased forced vital capacity and forced expiratory volume in 1 s, and increased levels of brain natriuretic peptide (indicative of left ventricle strain) after the oedema is resolved [46].…”
Section: Noncardiogenic Oedema and Haemoptysismentioning
confidence: 99%
“…Edema-prone individuals demonstrated a lower total lung tissue mass and thinner lung septae. Gempp et al 28 found that individuals prone to IPE demonstrated a high incidence of hypertension, and Peacher et al 29 reported a variety of common clinical comorbidities in 70% of individuals who showed evidence of IPE while diving (Table 1).…”
Section: Swimming-induced Pulmonary Edemamentioning
confidence: 99%